Chronic Pulmonary Melioidosis Masquerading as lung malignancy diagnosed by EBUS guided sheath technique. (2019) - Zaw, Kyi Kyi; Wasgewatta, Sanjiwika L.; Kwong, Kin Keung; Fielding, David; Heraganahally, Subash S.; Currie, Bart J.
Abstract: Diagnosis of pulmonary mass lesions can be challenging with several possible differentials. A 41-year-old Caucasian woman presented with intermittent non-specific chest pain on a background of 30 pack years of smoking history. A CT scan of the chest confirmed an opacity in the right lower lobe suspicious for primary pulmonary malignancy and PET scan showed moderate FDG avidity of the lesion. Conventional flexible bronchoscopy did not demonstrate an endobronchial lesion, Using Endobrochial Ultrasound (EBUS) Guide sheath technique, the lesion was localized in the posterior segment of the right lower lobe. Brushings, biopsies and washings were taken through the guide sheath, along with transbronchial cryobiopsy. Culture of bronchial brushings from the lesion on Ashdown's agar medium showed Burkholderia pseudomallei, confirming melioidosis. Treatment was with intravenous ceftazidime for 4 weeks, followed by oral sulphamethoxazole/trimethoprim for 3 months. During the follow up visits, the patient demonstrated significant improvement both clinically and radiologically.